Sustainable societal peace through the integration of bioethics principles and value-based education - Moorthy, Ravichandran; Selvadurai, Sivapalan; Gill, Sarjit Singh; Gurunathan, Angelina (MDPI AG, 2021)
We live in a world where hatred and conflicts divide individuals, society, and countries. Although all faith systems and school curriculums emphasize some degree of peaceful co-existence, love, and compassion, the real-world situation is indeed abysmal. How can a naturalistic and altruistic logic of bioethics enhance divine and human-centric values in enabling social cohesion? As such, this paper proposes the integration of bioethics and value-based education principles into the education curriculum to help mitigate social conflicts and promote harmony in society. By employing conceptual and theoretical reviews, the paper attempts to shed light on how these principles can help to mitigate hatred and conflicts in society. Further, through matrix analysis, the study shows the relationships between the four main bioethics principles, respect for autonomy, non-maleficence, beneficence, and justice, and the values expounded in value-based education. The study finds that by integrating bioethics principles into value-based education, learners are able to internalize the values of social cohesion and tolerance, and reflect these values in their learning experiences. Bioethics principles amplify the expressions of values promoted in value-based education, and this, in turn, motivates the learners to change from social conflict behaviors to social cohesion aptitude while dealing with others in society. Social cohesion enables individuals and groups to develop social bonds and societal peace ownership.